u0 = [1; -1; -1; -1] w0 = eye(4) -2 * (u0 * u0')/(u0' * u0) u1 = [1; -j; 1; j] w1 = eye(4) -2 * (u1 * u1')/(u1' * u1) u2 = [1; 1; -1; 1] w2 = eye(4) -2 * (u2 * u2')/(u2' * u2) u3 = [1; j; 1; -j] w3 = eye(4) -2 * (u3 * u3')/(u3' * u3) u4 = [1;(-1-j)/sqrt(2); -j; (1-j)/sqrt(2)] w4 = eye(4) -2 * (u4 * u4')/(u4' * u4) u5 = [1; (1-j)/sqrt(2); -j; (-1-j)/sqrt(2)] w5 = eye(4) -2 * (u5 * u5')/(u5' * u5) u6 = [1; (1+j)/sqrt(2); -j; (-1+j)/sqrt(2)] w6 = eye(4) -2 * (u6 * u6')/(u6' * u6) u7 = [1; (-1+j)/sqrt(2); j; (1+j)/sqrt(2)] w7 = eye(4) -2 * (u7 * u7')/(u7' * u7) u8 = [1; -1; 1; 1] w8 = eye(4) -2 * (u8 * u8')/(u8' * u8) u9 = [1; -j; -1; j] w9 = eye(4) -2 * (u9 * u9')/(u9' * u9) u10 = [1; 1; 1; -1] w10 = eye(4) -2 * (u10 * u10')/(u10' * u10) u11 = [1; j; -1; j] w11 = eye(4) -2 * (u11 * u11')/(u11' * u11) u12 = [1; -1; -1; 1] w12 = eye(4) -2 * (u12 * u12')/(u12' * u12) u13 = [1; -1; 1; -1] w13 = eye(4) -2 * (u13 * u13')/(u13' * u13) u14 = [1; 1; -1; -1] w14 = eye(4) -2 * (u14 * u14')/(u14' * u14) u15 = [1; 1; 1; 1] w15 = eye(4) -2 * (u15 * u15')/(u15' * u15)